2020
DOI: 10.21776/ub.jitode.2020.008.03.10
|View full text |Cite
|
Sign up to set email alerts
|

Jebel Qatrani as Geotourism Sites in Egypt: An Exploratory Study

Abstract: This research aims to identify the natural and geological features of Jebel Qatrani and to explore the role of geosite management in enhancing Jebel Qatrani as geotourism sites. A single case study was applied to reach the research aim. This research is based on a qualitative approach to obtain adequate information for achieving the research aim, direct observation was used for data collection. The results revealed that Jebel Qatrani has attractions such as fossils, rocks, mountains, and fossilized trees. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
1
0
2
Order By: Relevance
“…In several cases, researchers from foreign institutions were found, such as Nobukazu Nagakoshi (L. Hakim & Nagakoshi, 2008), David Reeve (Valeriani et al, 2020), Guillaume Tiberghien (Ristiawan & Tiberghien, 2021), and Kumiko Shishido (Sadguna et al, 2020), or where the member researchers are from different international institutions from the first researcher, such as the Hess et al, (2021) article, both of which were ignored, because the data collection only refers to the identity of the first researcher. Twenty-five international researchers were recorded from 15 countries: United States (Acharya, 2021), Australia (Ayoub, 2020;Prideaux & Tao, 2005;Zeng, 2005), Bangladesh (Bhuiyan & Ismail, 2018), Netherlands (Rindrasih, 2015), Bulgaria (Slavov & Palupi, 2019), Ethiopia (Eshete et al, 2020), Philippines (Abansi, 2012;Arreza & Esguerra, 2021;Era & Rosario, 2020;Espiritu & Guevarra, 2015;Luna, 2021), India (De, 2012;Dey, 2013;Vinodan, 2010), United Kingdom (Hess et al, 2021), Italy (Brida, 2008), South Korea (Anele & Sam-Otuonye, 2021), Egypt (Abdou et al, 2020), France (Loustaunau, 2018), Romania (Voda et al, 2019), and Thailand (Chaichompoo, 2011;Songkhla & Somboonsuke, 2012;Southiseng & Walsh, 2010). The authors noticed that the tendency of international scholars to publish their studies in national tourism journals is indicated to have increased in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…In several cases, researchers from foreign institutions were found, such as Nobukazu Nagakoshi (L. Hakim & Nagakoshi, 2008), David Reeve (Valeriani et al, 2020), Guillaume Tiberghien (Ristiawan & Tiberghien, 2021), and Kumiko Shishido (Sadguna et al, 2020), or where the member researchers are from different international institutions from the first researcher, such as the Hess et al, (2021) article, both of which were ignored, because the data collection only refers to the identity of the first researcher. Twenty-five international researchers were recorded from 15 countries: United States (Acharya, 2021), Australia (Ayoub, 2020;Prideaux & Tao, 2005;Zeng, 2005), Bangladesh (Bhuiyan & Ismail, 2018), Netherlands (Rindrasih, 2015), Bulgaria (Slavov & Palupi, 2019), Ethiopia (Eshete et al, 2020), Philippines (Abansi, 2012;Arreza & Esguerra, 2021;Era & Rosario, 2020;Espiritu & Guevarra, 2015;Luna, 2021), India (De, 2012;Dey, 2013;Vinodan, 2010), United Kingdom (Hess et al, 2021), Italy (Brida, 2008), South Korea (Anele & Sam-Otuonye, 2021), Egypt (Abdou et al, 2020), France (Loustaunau, 2018), Romania (Voda et al, 2019), and Thailand (Chaichompoo, 2011;Songkhla & Somboonsuke, 2012;Southiseng & Walsh, 2010). The authors noticed that the tendency of international scholars to publish their studies in national tourism journals is indicated to have increased in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…25 peneliti internasional berasal dari 15 negara: Amerika Serikat (Acharya, 2021), Australia (Ayoub, 2020;Prideaux & Tao, 2005;Zeng, 2005), Bangladesh (Bhuiyan & Ismail, 2018), Belanda (Rindrasih, 2015), Bulgaria (Slavov & Palupi, 2019), Etiopia (Eshete et al, 2020), Filipina (Abansi, 2012;Arreza & Esguerra, 2021;Era & Rosario, 2020;Espiritu & Guevarra, 2015;Luna, 2021), India (De, 2012;Dey, 2013;Vinodan, 2010), Inggris (Hess et al, 2021), Italia (Brida, 2008), Korea Selatan (Anele & Sam-Otuonye, 2021), Mesir (Abdou et al, 2020), Prancis (Loustaunau, 2018), Rumania (Voda et al, 2019), dan Thailand (Chaichompoo, 2011;Songkhla & Somboonsuke, 2012;Southiseng & Walsh, 2010). Dari frekuensi artikel bisa dilihat bahwa kecenderungan akademisi internasional untuk mempublikasikan kajian mereka pada jurnal pariwisata nasional terindikasi meningkat pada beberapa tahun terakhir.…”
Section: Diskusiunclassified
“…Selain dari 10 topik dengan porsi terbesar yang sudah dipaparkan di atas, kajian yang dilakukan oleh peneliti-peneliti juga mengangkat topik-topik menarik lainnya. Diantaranya adalah ekonomi pariwisata (Agfianto et al, 2019;Haryanto, 2014a;Kristiana & Nathalia, 2021;Lemy et al, 2021), agrotourism (Adhikerana et al, 2021;Azizah & Anom, 2020;Nisa' et al, 2014;Songkhla & Somboonsuke, 2012;Suharto, 2016;Widari et al, 2020), edutourism (Marzaman & Rasyid, 2020;Purnaya et al, 2018;Sadguna et al, 2020;Suharta et al, 2014), geotourism (Abdou et al, 2020;Darmaja et al, 2016;N. Wijaya et al, 2019;Wulung et al, 2020), culinary and gastronomy tourism (Darma Putra, 2014;Junianingsih et al, 2014;Nindita et al, 2019;Pitanatri, 2016;Ratnasari et al, 2020), spiritual tourism (Aditya et al, 2019;Baiquni & Heriani, 2021;Mau & Sukawati, 2019;Wiweka, 2014;Wulandari & Adikampana, 2018), ICT pada pariwisata (Acharya, 2021;Dewantara, 2019;I.…”
Section: Topik Lainunclassified